Models of Language Teaching and Humanizing Education - Rosida Tiurma Manurung (STKIP Singkawang, 2018)
Modern, digitalized, high tech, global era characterized by the development of sciences has transform human beings into heartless machines with no sense of humanity and no concerns to their surrounding environment. Therefore, education should be packed with loads that include the perspective of humanism. Education should not be interpreted as a mere class teaching-learning activity. Education should refer to the various processes and activities that should be productive; creative; develop skills, personality, integration, and excellence; and up to moral and spiritual reinforcement. Education shall be managed and directed with clear objectives, which are capable to develop positive values in learners. Education should be able to create figures with solid and proven character and personality both in the field of science and the humanities. Humanizing education means it is capable to produce human with sense of